Proceedings of the 2018 Designing Interactive Systems Conference 2018
DOI: 10.1145/3196709.3196760
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Situational Visual Impairments

Abstract: Mobile devices are a substantial part of our lives, supporting communication, work, and play. However, situational visual impairments (SVIs) can make completing tasks a challenge (e.g., browsing online in bright sunlight) and poorly designed content can cause or exacerbate SVIs. We surveyed 43 mobile content designers and ran four follow-on interviews to understand what designers currently do regarding SVIs, what resources they know of, and what is required to best support them in designing to reduce SVIs. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous work has discussed how it is important to include representative users when conducting research and that an induced situational impairment does not constitute the same experience as a permanent disability [48]. However, temporary and situational accessibility challenges can be used as a method to create empathy within developers [46] and also exists as an area where design challenges exist due to the increasing range of situations where technology is now used [52]. In our work we have shown that developers are aware of a large number of permanent challenges that users face within the areas of visual, communication, physical, cognitive, and emotional accessibility.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Previous work has discussed how it is important to include representative users when conducting research and that an induced situational impairment does not constitute the same experience as a permanent disability [48]. However, temporary and situational accessibility challenges can be used as a method to create empathy within developers [46] and also exists as an area where design challenges exist due to the increasing range of situations where technology is now used [52]. In our work we have shown that developers are aware of a large number of permanent challenges that users face within the areas of visual, communication, physical, cognitive, and emotional accessibility.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Prior work has investigated SVIs when using mobile devices under different lighting conditions [47]. Although designers are not well supported there are proposals for supporting them in addressing SVIs [48], which would be relevant for improving HSI. There is an opportunity here for designers of HSI to consider, and address, these concerns from the outset before they become issues for future applications.…”
Section: Designing For Surface Interactionsmentioning
confidence: 99%
“…Poorly designed content may also result in SVIs. Early-career designers typically do not address SVIs and require better support than what is currently available [52]. Reinecke et al [41] also identified that designers are under-supported when trying to understand a user group's varied perception of colour (influenced by inherited and acquired colour vision deficiency, as well as SVIs).…”
Section: Related Workmentioning
confidence: 99%
“…Early-career designers feel that current support for designing to reduce SVIs is lacking and they want improved guidelines, education, and digital design tools [52]. Although accessibility guidelines impose restrictions on design, it is possible to maximise creative freedom with a design tool [51].…”
Section: Implications For Designmentioning
confidence: 99%